Measuring, monitoring, and managing the green practices in mid-sized restaurants in China. Issue 1 (1st January 2016) - Ma, Jing; Ghiselli, Richard
ABSTRACT: This study explored the economic feasibility of adopting green practices in medium-sized restaurants in China. In particular, the short-term and long-term savings and environmental impact of adopting changes that do not require large investment were examined. Concepts from waste hierarchy and lean manufacturing served as the basis. Two mid-sized restaurants that were similar in terms of sales revenue, number of customers served, and payroll were selected. A number of incremental interventions were implemented and tested to identify the costs and/or benefits of sustainable management. Finally, this study made recommendations to restaurant owners, managers, and stakeholders.